ANALISIS PREFERENSI KONSUMEN KEDAI KOPI DI KOTA BANDARLAMPUNG - Rizky Agung Permadi; Wuryaningsih Dwi Sayekti; Zainal Abidin (Lampung University, 2022)
The growth of coffee shop is very fast recently in Bandarlampung with different characteristics that causes various consumer preference. This research aims to analyze consumer preferences as well as the level of performance and importance of coffee shop attributes in Bandarlampung. This study used a survey method involving 100 respondents with analytical tools, namely Conjoint Analysis, Customer Satification Index, and Important Performance Analysis. The research location was determined randomly, namely Bun Kopi, 20 Kopi, Diskusi Kopi, Kala Senja Café, and Rencana Kopi. The study shows that consumer preferences for coffee shops in Bandarlampung City were include complete facilities, such as cool and comfortable atmosphere, the taste of soft coffee drinks, modern industrialist building design, and fast service. The study also shows that customers are satisfied with the coffee shop. The taste attribute has the highest level of performance. Furthermore the attributes of facilities, services, and atmosphere have less performance, suggesting that these attributes need improvements. Meanwhile building design attribute is not priority for costumer. Key words: attribute, coffee shop, preference.